La garantie conventionnelle relative à l'automobile neuve et d'occasion : quelques aspects en droit de la consommation - L’Heureux, Nicole (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1982)
The sale of motor véhicules is generally subject to a conventional warranty. Many sections of the Consumer Protection Act cover such warranties. This paper focus on the impact of the principal dispositions of the Act affecting conventional warranties in the sale of new or used automobiles and the main problems which arise therefrom.